Revisiting Bond Breaking and Making in EuCo2P2: Where are the Electrons?. Issue 23 (21st February 2019) - Yannello, Vincent; Guillou, Francois; Yaroslavtsev, Alexander A.; Tener, Zachary P.; Wilhelm, Fabrice; Yaresko, Alexander N.; Molodtsov, Serguei L.; Scherz, Andreas; Rogalev, Andrei; Shatruk, Michael
Abstract: X‐ray absorption spectroscopy (XAS) was used to elucidate changes in the electronic structure caused by the pressure‐induced structural collapse in EuCo2 P2 . The spectral changes observed at the L3 ‐edge of Eu and K‐edges of Co and P suggest electron density redistribution, which contradicts the formal charges calculated from the commonly used Zintl–Klemm concept. Quantum‐chemical calculations show that, despite the increase in the oxidation state of Eu and the formation of a weak P−P bond in the high‐pressure phase, the electron transfer from the Eu 4f orbitals to the hybridized 5d and 6s states causes strengthening of the Eu−P and P−P bonds. These changes explain the increased electron density on P atoms, deduced from the P K‐edge XAS spectra. This work shows that the formal electron counting schemes do not provide an adequate description of changes associated with phase transitions in metallic systems with substantial mixing of the electronic states. Abstract : Under pressure : A combined study by X‐ray absorption spectroscopy and quantum‐chemical calculations demonstrates that formal electron counting rules are inadequate for the description of the re‐distribution of electron density upon pressure‐induced phase transition in the EuCo2 P2 intermetallic structure.